2000
DOI: 10.1603/0022-0493-93.4.1207
|View full text |Cite
|
Sign up to set email alerts
|

Damage to Nectarines by the Western Flower Thrips (Thysanoptera: Thripidae) in the Interior of British Columbia, Canada

Abstract: The phenology of damage by the western flower thrips, Frankliniella occidentalis (Pergande), on nectarines was investigated using sticky cards and direct sampling of buds between 1993 and 1995 in the interior of British Columbia, the most susceptible period for damage by western flower thrips to nectarines. The life stage responsible for damage and variation in susceptibility to damage of 11 different nectarine varieties were determined. To evaluate the predictive ability of 2 sampling methods, thrips were cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 16 publications
(17 reference statements)
1
14
0
4
Order By: Relevance
“…A separate study found that damage to nectarines by thrips is caused by feeding larvae rather than by oviposition activity or feeding by adult females (Pearsall 1999). The relationship between adult and larval densities and subsequent fruit damage in each orchard was also examined during that study.…”
Section: Discussionmentioning
confidence: 99%
“…A separate study found that damage to nectarines by thrips is caused by feeding larvae rather than by oviposition activity or feeding by adult females (Pearsall 1999). The relationship between adult and larval densities and subsequent fruit damage in each orchard was also examined during that study.…”
Section: Discussionmentioning
confidence: 99%
“…Their patterns of flight behaviour have not been studied to the extent of other insects such as aphids or locusts but, because of their growing economic importance in western Canada and also worldwide, it is important to examine their movement patterns more critically. Previous work identified that the western flower thrips is the most abundant species of thrips entering nectarine orchards in early spring in the interior of British Columbia, and the species to which the scarring of fruit may be solely attributed (P earsall , 2000; P earsall and M yers , 2001). Wild land which extends over vast areas of hillsides adjacent to orchards in this region is dominated by sagebrush ( Artemisia tridentata Nutt.)…”
Section: Introductionmentioning
confidence: 99%
“…2), as found in other crops, such as nectarines (Pearsall 2000), presumably because they feed more. The large reduction in damage (>90 %) in the presence of N. cucumeris (Fig.…”
Section: Discussionmentioning
confidence: 82%